Multitarget Phytocomplex: Focus on Antibacterial Profiles of Grape Pomace and Sambucus ebulus L. Lyophilisates Against Extensively Drug-Resistant (XDR) Bacteria and In Vitro Antioxidative Power - Vladimir S. Kurćubić; Vesna Đurović; Slaviša B. Stajić; Marko Dmitrić; Saša Živković; Luka V. Kurćubić; Pavle Z. Mašković; Jelena Mašković; Milan Mitić; Vladimir Živković; Vladimir Jakovljević (MDPI AG, 2024)
Objectives: This study was conceived with the aim of translating the experience and knowledge of the research group into the design and creation of multi-active phytocomplex cocktails from lyophilised winery by-products (Grape Pomace-GP) and weeds (Sambucus ebulus L., Dwarf Elder-DE). Methods: Quantification of bioactive molecules was performed by high-performance liquid chromatography (HPLC) method. Results: In the extract obtained from lyophilised GP, the most dominant component that was quantified was petunidin-3-glucoside. Prominent compounds that were quantified in DE extract were cyanidin derivatives. The total number of microorganisms in lyophilisates is low, but some of them still survive lyophilisation. Antibacterial activity was determined by microdilution, the minimum inhibitory concentration (MIC) of the tested bacteria ranged from 0.78 mg/mL to 25.00 mg/mL. Antibacterial susceptibility testing (AST) revealed that Klebsiella spp. and Acinetobacter baumannii complex are extensively drug-resistant (XDR). Conclusions: The GP + DE cocktail showed very strong AB power against both tested XDR bacteria. The total phenolic content and antioxidative effect (determined spectrophotometrically) indicate their linear correlation.